The Association Between Chest CT Severity Scores, CO-RADS, Vitamin D Levels and Other Laboratory Parameters of COVID-19 Patients - Kaan Alişar; Dilek Çetinkaya Alişar; Gonca Saglam; Serdar Karakullukçu (Galenos Yayinevi, 2022)
Objective:This study determined the correlation between several laboratory variables, chest computed tomography severity score (CTSS), and coronavirus disease-2019 (COVID-19) Reporting and Data System (CO-RADS) in COVID-19 patients.Materials and Methods:Ninety-one patients with COVID-19 infection verified by polymerase chain reaction test, presented to the emergency department with COVID-19 symptoms, and had a thoracic computed tomography (CT) scan at the time of admission were included in this retrospective study. 25-hydroxyvitamin D [25(OH)D] levels, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), D-dimer, glucose, ferritin, creatinine, alanine aminotransferase, aspartate aminotransferase, phosphorous, and calcium levels recorded and CO-RADS and CTSS data. The correlation of laboratory parameters with radiological findings was analyzed.Results:A positive correlation was found between CTSS and age, ESR, CRP, D-dimer while a negative correlation was found between CTSS and lymphocyte count. Patients with high CTSS levels had higher ESR, CRP, D-dimer, ferritin values and lower lymphocyte count, and lower calcium levels. Patients with typical CO-RADS involvement had higher sedimentation, CRP, glucose, and ferritin levels and lower lymphocyte count. No significant correlation was determined between the 25(OH)D level, CO-RADS, and CTSS.Conclusion:The results of this study highlight that the reduced lymphocyte count, high D-dimer, sedimentation, ferritin, and CRP levels are predictors of severe lung involvement in COVID-19 patients. Hypocalcemia can also be considered a marker of severe lung involvement evaluated by CT in COVID-19 patients. the association between vitamin D deficiency and COVID-19 pneumonia should be investigated in future studies.